Tinjauan Hukum Islam pada Praktik Mappasikarawa Dalam Perkawinan Suku Bugis - Alfina Damayanti; Ummi Salami (LPPM STIS Hidayatullah, 2022)
Mappasikarawa is a ritual after the marriage contract in the Bugis tradition. This study aims to find out how the Mappasikarawa ritual practice and the legal review of munakahat. This research is a field research with analytical descriptive research method. Data collection techniques using interview techniques to informants. The data that has been collected is processed by editing and analyzed based on a review of the munakahat law. After the marriage ceremony, the bridegroom is taken to the bride's room. The bridegroom is directed to sit opposite each other on the bed, then Pappasikarawa guides the bridegroom's thumb to touch the bride's body while praying for it. According to the munakahat legal review, the mappasikarawa ritual is permissible because the implementation of the ritual does not contain any harm and does not conflict with Islamic law. this is a true 'Urf.